The extent of the university student’s awareness of cybercrime (Journal of Human Sciences, 2024)
‏ This research aims to know the extent of the university ‎student’s ‎awareness and ‎knowledge of cybercrime, to ‎identify the type of  ‎cybercrime and the habits and patterns ‎of ‎Internet use among university students, and to identify ‎the statistically ‎significant ‎differences between the ‎average scores of the responses of the research sample ‎‎members about the extent of the ‎student’s knowledge and ‎awareness. Cybercrime ‎attributed to gender and age ‎variables. The most important results: ‎‎1_The extent of the university student’s knowledge and ‎awareness of cybercrime at the ‎Faculty of Arts, Sebha ‎University, ‎varies ‎‎2- There are no statistically significant differences ‎between the responses of the research ‎sample in the ‎extent of knowledge ‎and awareness of cybercrime due to ‎the gender ‎variable. ‎‎3- There are no statistically significant differences ‎between the responses of the research ‎sample in the ‎extent of knowledge ‎and awareness of cybercrime due to ‎the age variable‏.‏‏4-‏Hours: There are no statistically significant differences ‎between the responses of the ‎research sample in the ‎extent of ‎knowledge and awareness of cybercrime due to ‎the ‎variable number of people spend daily on the Internet. ‎‎5- There are no ‎statistically ‎significant differences between ‎the responses of the research sample in the extent of ‎‎knowledge and awareness ‎of cybercrime due to a variable ‎with who surfs the Internet ‎‎6- There are no statistically significant differences ‎between the responses of the research ‎sample in the ‎extent of knowledge ‎and awareness of cybercrime due to ‎the preferred ‎time variable for using the Internet. ‎‎7- There are no statistically significant differences ‎between the responses of the research ‎sample in the ‎extent of knowledge ‎and awareness of cybercrime due to ‎the variable What